GIS and public health - Cromley, Ellen K.; McLafferty, Sara, 1951- (New York : The Guilford Press, 2012)
"Authoritative and comprehensive, this is the leading text and professional resource on using geographic information systems (GIS) to analyze and address public health problems. Basic GIS concepts and tools are explained, including ways to access and manage spatial databases. The book presents state-of-the-art methods for mapping and analyzing data on population, health events, risk factors, and health services, and for incorporating geographical knowledge into planning and policy. Numerous maps, diagrams, and real-world applications are featured. The companion Web page provides lab exercises with data that can be downloaded for individual or course use"--
Machine generated contents note: Introduction1. Geographic Information Systems2. Spatial Data3. Spatial Databases for Public Health4. Mapping Health Information5. Analyzing Spatial Clustering of Health Events6. Analyzing Environmental Hazards7. Analyzing the Risk and Spread of Infectious Diseases8. Exploring the Ecology of Vector-Borne Disease9. Analyzing Access to Health Services10. Locating Health Services11. Health Disparities12. Public Participation GIS and Community Health.
Includes bibliographical references (p. 425-483) and index.
Keywords: Geographic information systems; Public health -- Data processing; SOCIAL SCIENCE / Human Geography; MEDICAL / Public Health; SCIENCE / Earth Sciences / Geography; TECHNOLOGY & ENGINEERING / Cartography; MEDICAL / Epidemiology; MEDICAL / General; MEDICAL / Health Care Delivery; MEDICAL / Health Policy